ATMO-vent: An adapted breathing atmosphere for COVID-19 patients. (October 2020) - Mathanlal, Thasshwin; Israel Nazarious, Miracle; Mantas-Nakhai, Roberto; Zorzano, Maria-Paz; Martin-Torres, Javier
Graphical abstract: Abstract: The ongoing worldwide pandemic of coronavirus disease 2019 (COVID-19), has been one of the most significant challenges to humankind in centuries. The extremely contagious nature of the SARS-CoV-2 virus has put forth an immense pressure on the health sector. In order to mitigate the stress on the healthcare systems especially to battle the crisis of mechanical ventilators, we have designed a modular, and robust DIY ventilator, ATMO-Vent (Atmospheric Mixture Optimization Ventilator) which can be fully mounted within two days by two operators. The ATMO-Vent has been designed using low-cost, robust, Commercial Off The Shelf (COTS) components, with many features comparable to a full-fledged ventilator. ATMO-Vent has been designed based on the United Kingdom Medicines & Healthcare products Regulatory Agency (UK-MHRA) guidelines for Rapidly Manufactured Ventilator System (RMVS), yet is scalable to the specific requirements of different countries. ATMO-Vent is capable of adjusting the Fraction of Inspiratory Oxygen (FiO2 ) levels, Tidal Volume (TV), frequency of breaths, Inspiratory/Expiratory ratio (I/E), Peak Inspiratory Pressure (PIP) and Positive End-Expiratory Pressure (PEEP). ATMO-Vent can operate in two modes – Continuous Mandatory Ventilation (CMV) using Volume-Controlled Ventilation (VCV) and in Assisted Control (AC) mode with pressure triggered by the patient. ATMO-Vent has undergone rigorous testing and qualifies under Class B Electric and Magnetic Compatibility (EMC) requirements of EN 55, 011 CISPR 11 standards.